PART II: OPTIMIZATION OF ISOSORBIDE DINITRATE SUSTAINED RELEASE LAYER IN ANTIHYPERTENSIVE BILAYER TABLET - TRIVEDI, HARSH; PATEL, KUNAL; OZA, NISHANT A.; SAGAR, SWATI (International Journal of Applied Pharmaceutics, 2020)
Objective: Aim of the present study was the optimization of the sustained release (SR) layer of isosorbide dinitrate (ISDN) 40 mg and compressed with the immediate-release (IR) layer of hydralazine hydrochloride (HHC) 25 mg to decrease the dosing frequency and development of a novel b. i. d dosage form. Methods: Drug excipients compatibility study was carried out by FT-IR and a preliminary study was conducted for screening of polymer. The amount of HPMC K100M (X1) and the amount of Polyoxtm WSR303 (X2) were chosen as independent variables in 32full factorial designs. While % cumulative drug releases at 1 h (Q1) (Y1), % cumulative drug release at 2 h (Q2) (Y2), % cumulative drug release at 4 h (Q4) (Y3) and % cumulative drug release at 6 h (Q6) (Y4), were taken as dependent variables and statistically evaluation by using sigma plot 13.0. In the present study, according to the U. S. P. 2007 the following constraints were used for the selection of an optimized batch: Q1=15% to 30%, Q2=50% to 70%, Q4=65% to 85% and Q6>75%. To validate the evolved mathematical models, a checkpoint batch was selected from its desirability value. Results: FT-IR spectra show that the drug and excipients were compatible with each other. The calculated F values found for Q1, Q2, Q4, and Q6 were 084.583, 038.188, 057.719, and 118.396, respectively. All Calculated F values are greater than the tabulated value for all dependent variables. Prepared checkpoint batch selected from its desirability value 1 and it gives a 93.40±1.29 % drug release within 6 h. Conclusion: This bilayer formulation of anti-hypertensive drugs decreases the dosing frequency of HHC and ISDN.